A Review on the Architecture of Software Defined Network. Issue 6 (1st November 2018) - Lin, Chuang; HU, Jie; Li, Guoliang; Cui, Laizhong
Abstract : Software defined network (SDN) is a promising network architecture which can simplify network management, ease deployment of network applications, and enable independent evolution of control plane and data plane. However, the separation of control plane and data plane intensifies performance concerns. In this paper, we review the performance of SDN from the perspective of I Ching which has a history of more than two and half millennia of commentary and interpretation, and provides inspiration to the worlds of business, military and religion. We utilize I Ching to model and abstract the architecture of SDN, and discuss the architecture and performance of SDN based on the statements of I Ching. Then we study current works and researches on the performance and architecture of SDN, and discuss the promising directions to the development and evolvement of SDN. Finally, we study common control functions in SDN and the deployment of SDN in diffierent networking settings.